Full annual monitoring of Subantarctic Emiliania huxleyi populations reveals highly calcified morphotypes in high-CO2 winter conditions [Dataset] - Rigual Hernández, Andrés Salvador; Trull, Thomas W.; Flores Villarejo, José Abel; Nodder, Scott D.; Eriksen, Ruth S.; Davies, Diana M.; Hallegraeff, G. M.; Sierro Sánchez, Francisco Javier; Patil, S. M.; Cortina, A.; Ballegeer, Anne-Marie Clara; Northcote, Lisa C.; et al. (Nature Publishing Group, 2020)
[EN]Supplement Table S1. a. Sampling dates and morphotype relative abundance of E. huxleyi coccolith assemblages collected in the surface layer at the SOTS site. b. Sampling intervals, fluxes and morphotype relative abundance and morphometric measurements of E. huxleyi coccolith assemblages intercepted by the sediment traps at the SOTS and SAM sites. Table S2. Environmental parameters measured at the surface layer of the SOTS site from August 2011 to July 2012. European Union's Horizon 2020, Marie Skłodowska-Curie Individual fellowship The dataset includes Supplementary Information, Table S1. : abundance, composition and morphometric data of E. huxleyi coccolith assemblages generated during the current study Table S2: environmental data Environmental parameters measured at the surface layer of the SOTS site from August 2011 to July 2012.